World money in ferment - Ponkshe, G. R. (Bombay : Lalvani Pub. House, 1971)
The main theme of the book, however, remain that of the evolution of the SDRs also known as paper gold. The scheme has therefore, been set out as simply as it could be in the appendix.
Includes index
uaa 25/01/2019
Loans.
Keywords: Monetary policy; Currency question; Foreign exchange; Inflation (Finance)